Ambient Manipulation of Perovskites by Alternating Electric Field toward Tunable Photovoltaic Performance. (19th August 2020) - Cheng, Zhendong; Ding, Dong; Song, Jingnan; Liu, Feng; Wang, Tun; Hu, Cheng; Ba, Lixiang; Wang, Jiayuan; Liu, Hong; Shen, Wenzhong
Abstract: With the rapid development of hybrid metal halide perovskites, controlling and understanding their growth processes have become an important but challenging task. In this paper, alternating electric field as an effective modulation method that acts on the intermediate state in perovskite formation under ambient conditions is introduced. The morphology and microstructure of the as‐formed perovskites can be effectively controlled by tuning simple physical parameters such as the frequency and amplitude, which have shown strong impact on the motion of ionic species and thus influences the formation of materials. Furthermore, the optic and electronic properties of the perovskite (such as the band position) can also be easily tuned by the field parameters. Finally, a conversion efficiency of 19.08% can be achieved in MAPbI3 device without any doping or additional treatment, with impressive ambient and thermal stability without encapsulation. This result has not only illustrated a new physical approach for material fabrication, but also facilitates deeper understanding of the formation mechanism and generally shed light to the development of more devices and materials. Abstract : The application of a low frequency alternating electric field on hybrid perovskite can evidently induce irreversible change of grains/crystal domains and distribution of ionic species in the bulk, leading to tunable opto‐electronic properties and significantly increased efficiency in inverted MAPbI3 cells without additional treatments and impressive intrinsic long‐term and thermal stability in air without encapsulation.